Characteristics and factors of concussion events for tacklers in collegiate rugby union - Suzuki, K.; Nagai, S.; Iwai, K.; Furukawa, T.; Mukai, N.; Miyakawa, S.; Takemura, M. (Scandinavian Journal of Medicine & Science in Sports, 2020)
The purpose of this study was to determine the factors related to the occurrence of concussion in rugby tacklers. Match video records showing tackles leading to concussion were used to identify injury-inciting events. Additionally, noninjury tackles by concussed tacklers (prior to concussion) and position-matched tacklers from the same matches were used as a control cohort. All tackles were coded according to the tackling characteristics. The odds ratio (OR) was reported by logistic regression. The results demonstrated that a side step of the ball-carrier reduced the risk of concussion for tacklers (OR = 0.13 [95% CI, 0.03-0.58]; P = .008). Conversely, the tackler's head/neck contacting the ball-carrier (OR = 18.62 [95% CI, 4.59-75.49]; P < .001) and not remaining bound to the ball-carrier since making initial contact (OR = 4.38 [95% CI, 1.69-11.34]; P = .002) were identified as risk factors for the concussion of tacklers. These results suggest that avoidance movements of the ball-carrier prior to tackling reduced the risk of concussion and that incorrect tackling techniques contributed to an increased occurrence of concussion. Furthermore, the probability of concussion for tacklers increased when their head was in front or to one side of the ball-carrier, and the direction of the tackle also affected the risk of concussion, especially from the side. Therefore, it is important to emphasize the tackler's head position in conjunction with the direction of tackle.